A novel flexible, conductive, and three-dimensional reduced graphene oxide/polyurethane scaffold for cell attachment and bone regeneration. (September 2022) - Sanati, Alireza; Kefayat, Amirhosein; Rafienia, Mohammad; Raeissi, Keyvan; Siavash Moakhar, Roozbeh; Salamat, Mohammad Reza; Sheibani, Sara; Presley, John F.; Vali, Hojatollah
Graphical abstract: Highlights: A green and cost-effective method is used for the fabrication of a flexible scaffold. Macro-porous 3DrGO/PU scaffold promotes osteogenesis by its graphene-modified structure. The interconnected scaffold reveals bioactivity, and provides high surface area for cell attachment and migration". Finite element simulation confirmed remarkable electrical potential of 3DrGO/PU scaffold. 3DrGO/PU scaffold showed high potential for in vivo bone regeneration in rat skull. Abstract: Development of conductive and three-dimensional scaffolds with elastic properties and shape-recovery capability for bone regeneration within irregular bone cavities has been challenging. Polyurethanes (PUs) are intrinsically elastic polymers; however, their mechanical performance, biocompatibility, and functionality need to be improved for application as implants and biomedical devices. Herein, application of a novel flexible, conductive, and three-dimensional polyurethane scaffold (3DPU), fabricated through coating a commercial PU foam with graphene oxide (GO) and its subsequent reduction with ascorbic acid, described as 3DrGO/PU, is investigated for bone regeneration. The 3DrGO/PU scaffold supported the growth and proliferation of mouse osteoblast cells (MG-63) with strong mineralization and cell attachment. It is likely that the electrically conductive macro-porous 3DrGO/PU scaffold, provides bioactivity and promote nucleation and growth of hydroxyapatite (HA) in the simulated body fluid. Experiments assessing in vivo bone formation in rat calvarial skull defects provided clear evidence for efficacy of the 3D scaffold for treatment of irregular bone defects. The results of this study are promising, as they present easy production of a cost-effective green fabricated scaffold. It also offers a potential for cell attachment and capture, to be used in future tissue engineering and even biosensing applications.